Wykorzystanie instrumentów pochodnych w przedsiębiorstwach agrobiznesu - Tomaszewski, Marek (Use of Derivative Instruments in Agribusiness Companies, 2005)
Agrarian production comprises three phases: gaining and transforming production factors and selling products.Great and rich agribusiness companies can reduce risk when they use derivative instruments. Derivative instruments can be also used in banks and by manufacturers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 365-369